KONSTRUKSI NARASI EKOLOGIS DAN KOLEKTIVITAS LOKAL SEBAGAI PENGGERAK PERUBAHAN SOSIAL LINGKUNGAN SUKU BADUY - Malik, Abdul (Jurnal Silva Samalas, 2023)
Human civilization, especially with its exploitative and unsustainable development activities, has made environmental issues an unavoidable discussion, including in Indonesia. Amid the ecological crisis, the Baduy indigenous community in Kanekes Village, Lebak Regency, Banten, maintains a distinctive way of relating to nature that is inseparable from their oral traditions and customary narratives. This study aims to analyze how ecological narratives are constructed within the Baduy community and how local collectivity functions as an agent driving environmental social change, both within the community and beyond it. This research employs a descriptive qualitative method through a literature review and narrative discourse analysis of scientific articles, reports, and documentation on the Baduy community published between 2019 and 2024. Data were analyzed through thematic categorization covering narrative reduction, presentation, and conclusion drawing. The results indicate that Baduy ecological narratives are constructed through the pikukuh (customary law), the three-zone forest classification, and taboo systems that are continuously reproduced through oral tradition and communal ritual. This narrative construction strengthens collective solidarity, which in turn becomes social capital that drives collective action in forest conservation, resistance to exploitative development, and the diffusion of ecological values to the wider public through media exposure. The study concludes that ecological narrative and local collectivity are mutually reinforcing components that position the Baduy not merely as passive holders of local wisdom, but as active agents of environmental social change.